Effect of Tween 80 and dimethyl sulfoxide on biosynthesis of L-lysine in regulatory mutants of Corynebacterium glutamicum - Konícek, J; Smékal, F; Konícková-Radochová, M (Folia microbiologica, 1991)
By using dimethyl sulfoxide or Tween 80 (1 or 0.2%), the production of L-lysine was increased by 20-28 and 23-25%, respectively, in regulatory mutant strains of Corynebacterium glutamicum. The stimulation observed is supposed to be caused by influencing cellular surface structures.
Keywords: Lysine; polysorbáty; mutace; dimethylsulfoxid; Mutation; lysin; Polysorbates; Dimethyl Sulfoxide; Corynebacterium